Molecular studies on susceptible and resistant Biomphalaria glabrata interacting with Schistosoma mansoni - Sowunmi, Kehinde Olukemi (2020)
Identification of molecular markers involved in the interaction between Biomphalaria glabrata and Schistosoma mansoni is crucial in the control of schistosomiasis as many of these molecules are likely to play important roles in host defence and parasite infectivity. This study attempted to identify and characterise molecules associated with compatibility polymorphisms in laboratory populations of B. glabrata with varying susceptibilities to S. mansoni. First, in a series of host-parasite compatibility experiments, a longitudinal study spanning almost three decades was completed. Analyses of data comprising the infection status of snail populations that had been monitored from 1991-2017 were used to determine the pattern of B. glabrata-S. mansoni compatibility in multiple, laboratory-maintained, host parasite combinations. This longitudinal study thus formed a basis for determining changes in the susceptibility and infectivity status of both the snail and parasite strains. Secondly, phylogeny of extant laboratory populations of three B. glabrata strains was established using the mitochondrial 16S ribosomal RNA gene. Thirdly, the three populations were characterised based on the sod1 gene. Fourthly, using SDS-PAGE, Western Blot analysis, and mass spectrometry, haemolymph and tissue glycoproteins of these three strains of B. glabrata were investigated for cross-reactivity against S. mansoni egg antigens. Results showed that B. glabrata snails and S. mansoni parasites display varying degrees of susceptibility and infectivity and co-evolved parasites and hosts are not necessarily better adapted to each other. Analysis of the 16S rRNA indicated Brazilian and Caribbean origins of the existing snail strains. Thirty-seven alleles were found to be segregating in the sod1 locus. There was no specific link to resistance in snails carrying the previously identified sod1 resistance-associated B allele. Mass spectrometry analysis of two differentially expressed protein bands from B. glabrata were identified to be partial haemoglobin and glutathione-S-transferase (GST-mu 1) and their possible involvement in cross-reactivity with parasite glycoconjugates is suggested. Identification of compatibility linked genes and/or gene products could find useful applications in development of therapeutic control agents for schistosomiasis.